Strategies and Models of Online Teaching: Exploring the Definition and Scope of Online Learning (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Online learning is synonymous to web based learning wherelearning is targeted through website only in internet or intranet. It has beenidentified as the new generation in the evolutionary growth of flexible, openand distance learning (Mishra, 2001). Armitage & O’Leary (2003, p 4)defined that online learning can also be defined as the use of digital mediaand technologies to support, distribute and enhance learning, assessment,teaching and evaluation. Contrary to that Naidu (2003, p 5) defined that onlinelearning defines the systematic use of communication technology and systematicuse of networked information in learning and teaching. Online learning is alsodefined as the enabled, mediated and delivered by electronic technology for theexplicit need of learning (Rossen and Hartley, 2001, p 2). W R Hambrecht &Co. (2000, p 8) described that in the corporate online learning report onlinelearning is defined as the large collection of processes and applicationconsisting of computer based le+arning, digital collaboration, virtualclassroom and web based learning (Mishra, 2001; Armitage & O’Leary (2003, p4); Naidu (2003, p 5); Rossen and Hartley (2001, p 2); and W R Hambrecht &Co. (2000, p 8) cited in Sharma and Mishra (2007, p 3-4).